2023
DOI: 10.1155/2023/6879022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PANoptosis-Based Prognostic Signature for Predicting Efficacy of Immunotherapy and Chemotherapy in Hepatocellular Carcinoma

Abstract: Background. PANoptosis has been a research hotspot, but the role of PANoptosis in hepatocellular carcinoma (HCC) remains widely unknown. Drug resistance and low response rate are the main limitations of chemotherapy and immunotherapy in HCC. Thus, construction of a prognostic signature to predict prognosis and recognize ideal patients for corresponding chemotherapy and immunotherapy is necessary. Method. The mRNA expression data of HCC patients was collected from TCGA database. Through LASSO and Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In esophageal cancer, PANoptosis mediated by sulconazole could induce oxidative stress and impair aerobic glycolysis to enhance radiosensitivity 21 . Xiong et al identified that PANoptosis might be an important indicator for efficacy of immunotherapy and chemotherapy in hepatocellular carcinoma (HCC) 22 . Wei et al also showed that PANoptosis was associated with HCC overall survival, immune infiltration, and immunotherapy response 23 , suggesting that PANoptosis showed promise to be a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal cancer, PANoptosis mediated by sulconazole could induce oxidative stress and impair aerobic glycolysis to enhance radiosensitivity 21 . Xiong et al identified that PANoptosis might be an important indicator for efficacy of immunotherapy and chemotherapy in hepatocellular carcinoma (HCC) 22 . Wei et al also showed that PANoptosis was associated with HCC overall survival, immune infiltration, and immunotherapy response 23 , suggesting that PANoptosis showed promise to be a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusive analysis revealed a significant correlation of SNHG7, an lncRNA, with COAD prognosis, tumor stage, lymph node metastasis, and drug resistance [ 106 ]. Reportedly through the construction of a prognostic signature to predict prognosis and recognize ideal patients for corresponding chemotherapy and immunotherapy, it was suggested that risk score could be a biomarker to predict the response to ICIs, TACE, and sorafenib therapy [ 107 ]. There are only few reports on experimental studies that link PANoptosis with drug resistance for antitumor purposes.…”
Section: Panoptosis and Drug Resistancementioning
confidence: 99%
“…In the past few decades, researchers have been devoted to finding drugs to treat cancer and have made tremendous progress in areas such as chemotherapy drugs ( Wang Y. et al, 2023 ), targeted drugs ( Isaksson et al, 2023 ; Jiang et al, 2023 ), immunotherapy ( Ren et al, 2023 ; Xiong et al, 2023 ; Yadav et al, 2023 ), sonodynamic therapy ( Wu et al, 2022 ), and radiation therapy ( Eyre-Walker and Stoletzki, 2013 ; Dumago et al, 2023 ; Moon et al, 2023 ). However, these anti-cancer strategies have shortcomings, including side effects and cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%